A casein hydrolysate increases GLP-1 secretion and reduces food intake. (30th June 2018) - O'Halloran, Fiona; Bruen, Christine; McGrath, Brian; Schellekens, Harriët; Murray, Brian; Cryan, John F.; Kelly, Alan L.; McSweeney, Paul L.H.; Giblin, Linda
Highlights: High throughput screening of dairy hydrolysates for GLP-1 modulation. Sodium caseinate, LFC25, increases GLP-1 secretion in a dose-dependent manner. Pilot scale quantities of LFC25 produced. LFC25 reduces cumulative food intake in murine trial. Abstract: In an effort to control weight gain, much attention has focused on the identification of bioactive peptides from food sources that induce satiety hormone secretion and increase the feeling of fullness. In this study, a screening platform identified a sodium caseinate hydrolysate, LFC25, that significantly increased calcium signalling in the enteroendocrine cell line, STC-1, and as a result increased secretion of the satiety hormone, GLP-1, in a dose-dependent manner. Administration of this hydrolysate to mice reduced the cumulative food intake over an eight hour period. To determine the feasibility of LFC25 as a food ingredient, production was scaled up to 10 L and spray-dried or freeze-dried without loss of bioactivity.